2020
DOI: 10.46421/2706-6568.37.2020.paper010
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations to BIM Approach for a Brazilian Infrastructure Contractor

Abstract: In recent years, Brazilian government issued a federal decree establishing the National Dissemination Strategy for Building Information Modelling (BIM) with the expectation that BIM will be disseminated in public works by 2028. In addition to this, the Brazilian Association of Technical Standards (ABNT) has set up a committee to generate and disseminate standardization involving the various aspects of BIM implementation. In this scenario, the objective of this paper is to investigate the BIM implementation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In the context studied, the general process was defined by the four steps indicated by the BIM Project Execution Planning Guide: identify BIM Goals and Uses, Design the BIM Project Execution Process, Develop the Information Exchanges and Define Supporting Infrastructure for BIM Implementation (Computer Integrated Construction Research Program, 2019). This framework was defined as a basis for the process due to its focus on implementation and operationalization of the BIM concept, compared to other guides that are more focused on giving recommendations to foster BIM diffusion (Borges et al ., 2020), but other frameworks might be used for this step, according to the context and constraints of each implementation. The following paragraphs detail the process conducted on the companies studied.…”
Section: Framework Proposalmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context studied, the general process was defined by the four steps indicated by the BIM Project Execution Planning Guide: identify BIM Goals and Uses, Design the BIM Project Execution Process, Develop the Information Exchanges and Define Supporting Infrastructure for BIM Implementation (Computer Integrated Construction Research Program, 2019). This framework was defined as a basis for the process due to its focus on implementation and operationalization of the BIM concept, compared to other guides that are more focused on giving recommendations to foster BIM diffusion (Borges et al ., 2020), but other frameworks might be used for this step, according to the context and constraints of each implementation. The following paragraphs detail the process conducted on the companies studied.…”
Section: Framework Proposalmentioning
confidence: 99%
“…Regarding construction companies, only 23.08% were using BIM (Sienge and Grant Thornton, 2020). Another study with Brazilian contractors showed that the majority of the respondents were at initial phase of BIM implementation (36.7%), with 13.3% of the companies not planning to implement BIM at all, and only 10% of the respondents stating they were in an advanced phase (Borges et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%